AN INTERNET OF THINGS ENVIRONMENTAL MONITORING IN CAMPUS - FEI LING, HAN (2017)
A remote temperature and humidity monitoring system is developed to measure the temperature, humidity and calculate the heat index value at different locations in the Universiti Teknologi PETRONAS (UTP) campus. This system incorporates the Internet of Things (IoT) and Wireless Sensor and Actuator Networks (WSANs) concept. The temperature and humidity sensors are used to measure the environmental conditions and the information is sent to the Cloud over the Internet via wireless communication. Feedback is provided based on the data analysis of the collected data in which it will activate the actuator. This system is categorized as the environmental monitoring system where the weather conditions, specifically the temperature and humidity of the surrounding, are measured.